Development and gamification of a neurofeedback application to support anxiety treatment - Silva, Pedro Folque de Gouveia Pestana da (2019)
Anxiety disorder is one of the most common mental illness, affecting 264 million people worldwide. Current treatments are limited because they cause side effects and/or require long therapeutic periods. Neurofeedback (NFB) has been associated with the reduction of anxious symptomatology but typically uses unappealing therapeutic interventions. In this work a game was developed, Anxiety Destroyer, using procedures of gamification adapted to the NFB, with the goal of providing a guided, immerse and efficient treatment, to be used at home. The lean method was applied to the development process by construction-measurement-learning of value propositions. Thirty people were studied, which performed up to 8 NFB sessions for 35 minutes, totalling 185 sessions, 108 hours. Three groups of 10 individuals were created, one group with frontal alpha asymmetry (Alpha Asymmetry (ALAY)) protocol (F4-F3), another with asymmetry between AF4 and AF3 channels (AF) for hairless skin usage and another control group, with increased alpha in F4 and F3 (F+). The Beck Anxiety Inventory (BAI) was applied to assess anxiety. The Game Experience Questionnaire (GEQ) was used to evaluate game experience in different versions, which were adapted to the needs of the user. The ALAY group significantly increased the asymmetry (p <0.05) (reduction of the anxiety biomarker), with a corresponding significant reduction (p <0.01) in the anxiety reported by BAI after NFB training. The AF group showed a decrease in the frontal alpha asymmetry, and the F+ a slight increase, respectively confirmed by the increase and decrease of the BAI. The GEQ did not show better gaming experience throughout sessions. An increase of the sample size is required to confirm these results, inclusively since some individuals in the AF and F+ groups abandoned treatment because of no perceived effects. However, this study suggests the effectiveness of the gamified application in the treatment of anxiety.